The influence of soil management on soil health : an on-farm study - Williams, Hanna (SLU/Dept. of Soil and Environment, 2018)
The capacity of a soil to provide ecosystem services without negative impacts on the environment is defined as soil health. Healthy soils are a fundamental resource for agricultural production and our ability to feed a growing global population. We must therefore increase our understanding of how soil health is affected by soil management. This study investigated soil health on 20 farms in the south of Sweden, using samples of topsoil from farm fields and from unmanaged soil adjacent to the sampled field at each site. Soil health was assessed using the following physical, chemical, and biological indicators: wet aggregate stability, soil protein content, active carbon, soil respiration, and soil organic matter. We designed a soil management index based on crop diversity, avoidance of mechanical soil disturbance, and application of organic amendments, and evaluated its effect on individual soil health indicators and overall relative soil health. The results of this study showed that soil health was poorer in agricultural fields than unmanaged soils. Furthermore, a high soil management index resulted in higher values for individual soil health indicators. However, soil health indicators differed in how sensitive they were to soil management. We found that wet aggregate stability and soil protein content had a high sensitivity to soil management. Active carbon, soil respiration and soil organic matter content were less sensitive to soil management and more dependent on soil texture. Lastly, the results show that a high soil management index resulted in an improved overall soil health relative to the potential soil health represented by the unmanaged soil. Our results show that it is possible to promote soil health through high crop diversity, avoidance of mechanical soil disturbance, and application of organic amendments